Enumeration of petroleum-degrading microorganisms. - Walker, J D (1976)
A variety of factors, including concentration of oil, antibiotics, dyes, and inoculum washes, were examined to determine their effect on the total counts of microorganisms on oil-containing media. The media found to be best for enumerating petroleum-degrading microorganisms contained 0.5% (vol/vol) oil and 0.003% phenol red, with Fungizone added for isolating bacteria and streptomycin and tetracycline added for isolating yeasts and fungi. Washing the inoculum did not improve recovery of petroleum degraders. Specifically, silica gel-oil medium and a yeast medium are recommended for enumeration of petroleum-degrading bacteria and yeasts and fungi, respectively. It is suggested that counts of petroleum degraders be expressed as percentage of the total population rather than total numbers of petroleum degraders per se. Incubation temperature and presence of oil was found to influence the numbers of petroleum-degrading microorganisms at a given sampling site.